Smile - Telgemeier, Raina (New York : Graphix, 2010)
From sixth grade through tenth, Raina copes with a variety of dental problems that affect her appearance and how she feels about herself.
Keywords: Youth -- Comic books, strips, etc -- Dental care; Dental care -- Comic books, strips, etc; Self-esteem -- Comic books, strips, etc; Beauty, Personal -- Comic books, strips, etc; Orthodontic appliances -- Comic books, strips, etc; Dental care -- Cartoons and comics; Self-esteem -- Cartoons and comics; Beauty, Personal -- Cartoons and comics; Orthodontic appliances -- Cartoons and comics; Comic books, strips, etc